Intermediate Outcomes after Rapid Deployment Aortic Valve Replacement in Multiple Valve Surgery - Schlömicher, Markus; Bechtel, Matthias; Taghiyev, Zulfugar; Naraghi, Hamid; Haldenwang, Peter Lukas; Moustafine, Vadim; Strauch, Justus T. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Multiple valve surgery is associated with significant higher operative risks. Reduced cross-clamp and cardiopulmonary bypass times in multiple valve surgery may potentially be beneficial as they can be considered independent risk factors for increased morbidity and mortality following cardiac surgery. We report first intermediate outcomes of the Edwards Intuity valve system (Edwards Lifesciences, Irvine, California, United States) in combined proceduresMethods Fifty-eight patients underwent rapid deployment aortic valve replacement with concomitant mitral valve surgery between January 2014 and November 2017 in our institution. The valve was assessed echocardiographically after 12 months. The median follow-up was 1.7 years with a cumulative follow-up time of 115.3 patient years.Results The mean age was 73.5 ± 6.2 years and the mean logistic Euroscore was 11.6 ± 3.1%. Concomitant mitral valve repair was performed in 43 cases (74.1%), and mitral valve replacement in 15 cases (19.0%). The mean cross-clamp time was 93 ± 21 minutes along with a mean bypass time of 118 ± 24 minutes. All-cause mortality after 30 days was 8.6%. Overall actuarial survival at 1 year was 87.2 ± 4.5% and after 2 years 82.8 ± 5.3%, respectively.Conclusions Rapid deployment aortic valve replacement in multiple valve surgery can be performed safely with good intermediate outcomes in elderly, high-risk patients.
Keywords: echocardiography; heart valve surgery; mitral valve surgery